Exporting Urban Korea? Reconsidering the Korean Urban Development Experience (Taylor & Francis, 2020)
A detailed examination of the "Korean development model" from its urban dimension, evaluating its sociopolitical contexts and implications for international development cooperation. There is an increasing tendency to use the development experience of Asian countries as a reference point for other countries in the Global South. Korea's condensed urbanization and industrialization, accompanied by the expansion of new cities and industrial complexes across the country, have become one such model, even if the fruits of such development may not have been equitably shared across geographies and generations. The chapters in this book critically reassess the Korean urban development experience from regional policy to new town development, demonstrating how these policy experiences were deeply rooted in Korea's socioeconomic environment and discussing what can be learned from them when applying them in other developmental contexts. This book will be of great interest to scholars and researchers in the field of urban studies and developmental studies in general, and in Korea's (urban) development experience in particular.
English
Keywords: Politics & government; Regional studies; Urban & municipal planning; China; Infrastructure; Seoul; Singapore; Smart City; Urban Transformation